Supply Pressure and the Export-Import Performance in the Japan-U.S. Bilateral Trade - Onitsuka, Yusuke (Washington, D.C. : International Monetary Fund, 1994)
The paper examines the effects of the supply pressure of the exports in the Japan-U.S. bilateral trade. A simultaneous equation approach with a Almon lag structure is adopted. Two factors of supply pressure, id est, full-employment capacity and inventory are specified, and positively-sloped export supply functions with these two shift factors are successfully estimated. While capacity is positively correlated with exports, the inventory is often negatively correlated. It is also shown that export supply pressure is much stronger in Japan's exports than in the U.S. exports, and that supply pressure often affects exports with a lag structure spreading over twelve quarters.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet